2017
DOI: 10.22159/ijpps.2017v9i6.16285
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Immuno-Modulatory Effect of Moringa Oleifera Flowers

Abstract: Objective: This study evaluates the anti-inflammatory activities of different solvent extracts of Moringa oleifera flowers using carrageenan-induced mice paw edema.Methods: Soxhlet extraction method was employed in this study to extract the crude phytochemicals. Phytochemical analysis testing of Moringa oleifera extracts was performed to identify the presence of various phytoconstituents based on the standard procedures. The anti-inflammatory activity was evaluated using acute inflammatory model carrageenan-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The use of androgens (testosterone, testosterone propionate, enanthate) or estrogens (estradiol valerate) is a technique to develop a type of physiopathology in animal models similar to women with PCOS (Anesetti & Chávez‐Genaro, 2016 ). Insulin resistance (IR) due to elevated levels of free fatty acids and hyperglycemia leads to the activation of reactive oxygen species (ROS) and enhances oxidative stress (Velaga et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of androgens (testosterone, testosterone propionate, enanthate) or estrogens (estradiol valerate) is a technique to develop a type of physiopathology in animal models similar to women with PCOS (Anesetti & Chávez‐Genaro, 2016 ). Insulin resistance (IR) due to elevated levels of free fatty acids and hyperglycemia leads to the activation of reactive oxygen species (ROS) and enhances oxidative stress (Velaga et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This increase will cause activation of the serine phosphorylation pathway in the IRS and will inhibit the formation of PI3K which will compensate for the occurrence of hyperandrogens. 10 …”
Section: Introductionmentioning
confidence: 99%
“…This increase will cause activation of the serine phosphorylation pathway in the IRS and will inhibit the formation of PI3K which will compensate for the occurrence of hyperandrogens. 10 Several studies have reported that PCOS-IR mouse models can be made by subcutaneous injection of testosterone propionate in combination with a high-fat diet. 11,12 These mice have features similar to the pathology of PCOS and endocrine disorders but externally added androgens can affect the endocrine level of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Each part of Moringa oleifera has shown medicinal value, and the leaves of Moringa oleifera are the most extensively studied. Moringa oleifera leaf holds some certain therapeutic potential for many diseases, for instance, chronic hyperglycemia, hyperlipidemia [12], immune regulation [13], hypertension [14], cancer [15], liver disease, inflammation, etc. [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%